Simulink Model for Piece Wise Linear Approximation of Memristor - Ahmet SOLAK; Saadetdin HERDEM (International Journal of Applied Methods in Electronics and Computers, 2016)
Memristor is a passive circuit element which firstly presented to science world by Leon Chua in 1971. Chua showed a missing link among four fundamental circuit variables which generate basic passive circuit elements. Chua described this missing link between charge and flux, named it as memristor. Memristor is firstly realized by Stanley Williams and his team from HP (Hewlett Packard) research laboratories in 2006. In this study, doped and undoped TiO 2 are sandwiched between two Pt layers in nano scale. And this element demonstrated voltage-current characteristic like memristor. Physically implementation of memristor is announced with a paper to science world in 2008. The studies about memristor have quite increased along with this study. In this paper, a new PWL (Piece Wise Linear) memristor model is obtained thereby linearizing current-voltage characteristic of memristor. The equivalent circuit is derived from this model, built in Simulink and results are observed. The results are compared with other studies in literature and obtained results have been shared.